Giant Cell Tumor of the Capitate Bone - Afshar, Ahmadreza; Tabrizi, Ali; Aidenlou, Ali; Abbasi, Ata (Journal of Hand and Microsurgery, 2018)
This case report describes a 16-year-old female patient with a giant cell tumor in her right capitate bone. The tumor was removed by intralesional curettage. A high-speed burr was used to extend the margins of the curettage, and alcohol irrigation was used for adjuvant therapy. The cavity of the capitate was filled with allogenic bone graft. There was no recurrence after 2 years of follow-up, and the right wrist radiographs demonstrated healing of the lesion.
Keywords: capitate; giant cell tumor of bone; hand tumor; wrist tumor